Sociodemographic and knowledge profile of patients with type 2 diabetes mellitus at Royal Prima General Hospital - Naibaho, Iren Theresia Melati Br; Lister, I Nyoman Ehrich; Girsang, Ermi (Buletin Kedokteran & Kesehatan Prima, 2025)
This study utilized a descriptive design with a cross-sectional approach, conducted from April to May 2024 at Royal Prima General Hospital, Medan. A total sampling technique was employed, including all 64 registered T2DM patients. Sociodemographic and knowledge data were collected via questionnaire and analyzed using univariate analysis to generate frequency distributions and percentages. The findings revealed that the majority of respondents were aged ≥45 years (62.5%), male (53.13%), had a low education level (≤9 years of schooling) (53.13%), and were unemployed (51.56%). Nevertheless, a majority of patients (62.5%) possessed a good level of knowledge regarding their disease. The profile of T2DM patients is consistent with that of a socioeconomically high-risk population. The high level of knowledge observed in the majority of patients may not guarantee optimal disease management due to potential structural and economic barriers. Therefore, intervention strategies for T2DM must be multifaceted, moving beyond education to address socioeconomic obstacles that impede the translation of knowledge into effective self-care behaviors.